Pengaruh Customer Experience Terhadap Repurchase Intention (Studi Pada Seluruh Coffee Shop Di Kota Mataram) - Amiruddin Kalbuadi; Lale Puspita Kembang (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Coffee is a popular drink enjoyed by all ages. Coffee plantations in Indonesia have contributed to the country's long coffee production and economic growth history. According to the ICO, Indonesia ranks sixth globally for coffee consumption, with a total consumption of 4.6 million 60 kg/lb in the 2016-2017 range. This study aims to see the effect of Customer Experience, which consists of sense, feel, thinking, act, and relation, in influencing the repurchase intention behavior of coffee shop consumers in Mataram City. This study uses a quantitative approach with the type of associative research because it examines the effect of the independent variables on the dependent variable. The sampling technique uses non-probability and purposive sampling to obtain the characteristics of the respondents to be studied. The number of respondents reviewed amounted to 180 people. The data collection technique uses a questionnaire with a questionnaire as a data collection tool. The instrument test uses validity and reliability tests. The model feasibility test uses the classic assumption test, consisting of the normality, multicollinearity, and heteroscedasticity tests. The analysis tool uses multiple linear regression analysis. Hypothesis testing using the t-test for partial test and F test for simultaneous test. The results obtained are that there is an influence between the independent variables consisting of sense, feel, think, act, and relate to the dependent variable repurchase intention either partially or simultaneously so that all research hypotheses are accepted.